2011
DOI: 10.1186/1477-7827-9-126
|View full text |Cite
|
Sign up to set email alerts
|

miRNA regulation of cytotoxic effects in mouse Sertoli cells exposed to nonylphenol

Abstract: BackgroundIt is known that some environmental chemicals affect the human endocrine system. The harmful effects of endocrine disrupting chemical (EDC) nonylphenol (NP) have been studied since the 1980s. It is known that NP adversely affects physiological functions by mimicking the natural hormone 17 beta-estradiol. In the present study, we analyzed the expression of miRNAs and their target genes in mouse Sertoli TM4 cells to better understand the regulatory roles of miRNAs on Sertoli cells after NP exposure.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The miRNA microarray results indicated that 8 miRNAs (miR-374b-5p, miR-362-5p, miR450a-5p, miR-193a-3p, miR-128-3p, miR-29b-3p, miR-199a-5p, and miR-miR-181a) involved in both azoospermia and non-obstructive azoospermia were dysregulated in MC-LR-treated Sertoli cells. miR-374b-5p, miR-128a-3p, miR-29b-3p and miR-199a-5p have been reported to be altered in nonylphenol-induced Sertoli cell toxicity (Choi et al, 2011). The dysregulation of miR-374b-5p, miR-193a-3p, miR-128-3p and miR-181a was also found in the semen of patients with azoospermia and asthenozoospermia (Wang et al, 2011).…”
Section: Disscussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The miRNA microarray results indicated that 8 miRNAs (miR-374b-5p, miR-362-5p, miR450a-5p, miR-193a-3p, miR-128-3p, miR-29b-3p, miR-199a-5p, and miR-miR-181a) involved in both azoospermia and non-obstructive azoospermia were dysregulated in MC-LR-treated Sertoli cells. miR-374b-5p, miR-128a-3p, miR-29b-3p and miR-199a-5p have been reported to be altered in nonylphenol-induced Sertoli cell toxicity (Choi et al, 2011). The dysregulation of miR-374b-5p, miR-193a-3p, miR-128-3p and miR-181a was also found in the semen of patients with azoospermia and asthenozoospermia (Wang et al, 2011).…”
Section: Disscussionmentioning
confidence: 96%
“…Computational predictions indicate that more than one third of all human genes may be the targets of miRNA (Krek et al, 2005). Recent research has demonstrated that gene expression of Sertoli cells is regulated by sophisticated mechanisms including epigenomic regulation by miRNAs (Choi et al, 2011). Accumulating evidence has proven a crucial role of miRNAs in MC-induced cancer progression and embryonic development (Xu et al, 2012;Zhao et al, 2012).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, microRNAs (miR) are involved in proper differentiation of primordial germ cells (PGCs) and have been shown to be dysregulated in testicular germ cell tumors [32]. Alterations in miR expression have been observed in mouse Sertoli cells that were exposed to nonyl-phenol [33]. Other EDCs, such as BPA and DDT have also been linked to altered miR expression in estrogen-responsive human breast cancer MCF-7 cells and in placental cell lines, respectively [32].…”
Section: 00 What Is An Edc?mentioning
confidence: 99%
“…The effects of prenatal EDCs on developmental expression of microRNAs have not been studied in the hypothalamus, but their effects have been shown in other tissues including mouse Sertoli cells (22), whole brains, and livers (23); rat penile shafts (24) and hippocampal cultures (25); and human breast carcinoma (26, 27) and placental cell lines (28). In the current study, we addressed whether a class of prenatal EDCs affect the expression of microRNAs during brain sexual differentiation following prenatal exposure of rats to A1221, a mixture of polychlorinated biphenyls (PCBs) that has previously been shown to perturb expression of sexually dimorphic genes in the brain and cause reproductive and behavioral phenotypic changes in adulthood (4, 5, 2932).…”
Section: Introductionmentioning
confidence: 99%